Paradoxes of the Killer’s Identity - Sireikis, Augustas (Jaunųjų mokslininkų darbai, 2024)
The article examines a short story “My Friend Sigitas” [Mano draugas Sigitas] by Alvydas Šlepikas through the lens of Jacques Lacan’s structural psychoanalysis. The main focus is placed on identification, which, unlike in the classical tradition of psychoanalytic literary criticism, is examined not as a mental act of the author or reader, but as an action of verbal communication, embedded in the literary text itself. Thus, a seemingly simple and funny story about the death of a friend is revealed to be rendered around a paradox: through various discursive operations, the homodiegetic narrator simultaneously tries to accept and reject the accusation of murder. In this way, contrary to a common assumption, a traumatic structure of discourse is associated not with a victim or witness, but the accused, i.e., the position of a potential murderer. The latter is analysed neither from the legal perspective, which due to the narrator’s justification to the addressee would be natural in empirical reality, nor by speculating about the inner experiences of the subject, as if he were a real person. By comparing this research strategy with possible alternatives, we demonstrate the differences between psychological and psychoanalytical interpretation of literature.
Keywords: psychoanalysis; identification; Lacan; Šlepikas; death